2022
DOI: 10.1177/20406223221117971
|View full text |Cite
|
Sign up to set email alerts
|

Association of Barrett’s esophagus with Helicobacter pylori infection: a meta-analysis

Abstract: Background and Aims: Barrett’s esophagus (BE) is the only recognized precursor for esophageal adenocarcinoma. Helicobacter pylori ( H. pylori) infection is a major contributing factor towards upper gastrointestinal diseases, but its relationship with BE remains controversial. Some previous studies suggested that H. pylori infection negatively correlated with BE, while others did not. This may be attributed to the difference in the selection of control groups among studies. The present meta-analysis aims to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Fig 2 visually displays the significant publication bias present in our chosen papers. We employed the Leave-one-out method for sensitivity analysis to remove the most extreme outlier studies [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fig 2 visually displays the significant publication bias present in our chosen papers. We employed the Leave-one-out method for sensitivity analysis to remove the most extreme outlier studies [ 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…We conducted a search for all publications in the gastroparesis field in the Science Citation Index-Expanded (SCIE) database in the WOS Core Collection (WOSCC), for the period spanning from database inception to November 16, 2022. The search terms were formulated based on the clinical experience, medical subject headings (MeSH), and published articles [ 18 , 19 ], and a title search was finally performed on the retrieved articles to avoid the inclusion of a large number of unrelated articles [ 20 22 ]. The search formula was finally set as follows: TI = (Gastropares*) OR TI = (Gastric Stas*).…”
Section: Methodsmentioning
confidence: 99%
“…[40][41][42] Table 2 summarizes five meta-analyses of observational studies evaluating the association between H. pylori infection and BE. 43- 47 Wang et al showed no significant difference in the overall prevalence of H. pylori infection in BE and healthy controls. 43 Subgroup analysis favored a lower prevalence of H. pylori infection in BE patients.…”
Section: H Pylori and Bementioning
confidence: 98%